Investment Law Policy in Efforts to Develop Border Regions for the Realization of a Welfare State - Rietha Lieke Lontoh (CV. AFDIFAL MAJU BERKAH, 2022)
Its management and utilization must be in line with the constitutional mandate, namely that its management is intended for the greatest prosperity of the people. Attracting investors to invest in the regions is not an easy job because the regions are not the only players, but there are national and global factors that need to be taken into account, such as political stability, national security and resilience, the rule of law and the consistency of the regional autonomy program. Meanwhile, global factors, economic globalization and the opening of new markets are two things that business players in the region must immediately catch. The purpose of this research is to examine the investment law policy that is fair in the border area. The research method uses a normative juridical research method that is descriptive analytical. The results of the study The author argues that the influence of policy on investment activities in Indonesia is quite large, especially investment or investment which has an important role in the welfare of the community. The concept of a welfare state law must be a reflection of the state's responsibility in implementing state control which is the authority of the central government whose real goal is to maximize the welfare of the people, so that state authority by involving investors must be understood as a tool or facility to achieve that goal, so that the implementation of state control so far has not been abused and can prosper the people from the aspect of national resilience.